How Swiss primary students interpret a national monument. (26th October 2018) - Mathis, Christian; Gollin, Kristine
Since historical monuments are often difficult to interpret, this study commences with the questions, how do students understand historical monuments and in what ways are they able to describe and interpret them? The focus of our paper is a monument showing Arnold Winkelried, a leading Swiss national figure that nine Swiss students of Grades 5 and 6 studied. Winkelried is a legendary Swiss hero who sacrificed himself to bring about Swiss victory over the Austrian Habsburgs in the Battle of Sempach in 1386. As an iconic, symbolic source of Swiss national cultural heritage, he is representative of the establishment of the young Swiss Federation's history culture in the second half of the nineteenth century. The study's mainly oral research data was collected by means of focus groups (Bohnsack, 2010). The discussions with the students were recorded, transcribed and analysed using a documentary method (Straub, 1999), that is, we reconstructed typical patterns of description. The findings first indicated that students find it difficult to observe and describe such monuments appropriately. Indeed, the students tended to begin the process by guessing what they were observing. Second, the findings show that through the interviewer's prompts – accurate observations and descriptions – during the focus group sessions, students can activate prior knowledge and thus engage with the historical topic.